Seizures Induced by Desloratadine, A Second-Generation Antihistamine: Clinical Observations - Cerminara, Caterina; El-Malhany, Nadia; Roberto, Denis; Lo Castro, Adriana; Curatolo, Paolo (Neuropediatrics, 2013)
Some clinical experiences indicate that H1-antihistamines, especially first-generation H1-antagonists, occasionally provoke convulsions in healthy children as well as epileptic patients. Desloratadine is a frequently used second-generation antihistamine considered to be effective and safe for the treatment of allergic diseases. We describe four children who experienced epilepsy associated with the nonsedating H1-antagonist desloratadine and discuss the neurophysiologic role of the central histaminergic system in seizure susceptibility. In conclusion, we recommend caution in treating epileptic patients with the histamine H1-antagonists, including second- and third-generation drugs that are frequently referred because they are considered to be nonsedating antihistamines.
Keywords: seizure; desloratadine; antihistamine; epilepsy